Pulmonary nocardiosis caused by Nocardia blacklokiae in an immunocompetent patient. (2020) - Ito, Yuhei; Tanigawa, Motoaki; Yaguchi, Takashi; Toyoshima, Hirokazu; Iwamoto, Keisuke; Nigi, Akina; Itani, Hidetoshi; Kondo, Shigeto; Tokui, Toshiya; Sasano, Hajime
Abstract: A subset of Nocardia isolates, previously belonging to N. transvalensis, has recently been given the new species designation N. blacklokiae . Here we report a case of pulmonary nocardiosis caused by N. blacklokiae in a 52-year-old immunocompetent woman presenting with low-grade fever and fatigue. The isolated Nocardia strain was resistant to sulfamethoxazole-trimethoprim and amikacin, but susceptible to amoxicillin-clavunate, ceftriaxone, clarithromycin and linezolid. With amoxicillin-clavunate treatment, the patient recovered and her condition remained stable, although recurrence occurred after cessation of the initial treatment. While infection by Nocardia is rare, clinicians should be aware of its resistance to antimicrobials including amikacin and sulfamethoxazole-trimethoprim.